Electronic Continuous Pain Measurement vs Verbal Rating Scale in gynaecology: A prospective cohort study. (January 2021) - Louwerse, Marjoleine D.; Hehenkamp, Wouter J.K.; van Kesteren, Paul J.M.; Lissenberg, Birgit I.; Brölmann, Hans A.M.; Huirne, Judith A.F.
Abstract: Objective: To compare pain measured with a new electronic device – the Continuous Pain Score Meter (CPSM) – and the Verbal Rating Scale (VRS) during gynaecological procedures in an outpatient setting, and to correlate these outcomes with baseline anxiety and patient (in)tolerance to the procedure. Study design: This prospective cohort study was undertaken in two centres: a university hospital and a large teaching hospital in The Netherlands. Patients undergoing an outpatient hysteroscopy, colposcopy or ovum pick-up procedure for in-vitro fertilization in one of the two participating hospitals with availability of the CPSM were included. Pain was measured by both the CPSM and the VRS. Patient tolerance to the procedure was reported. Various outcomes of the CPSM were compared with those of the VRS and related to baseline anxiety scores. Results: Ninety-one of 108 included patients (84 %) used the CPSM correctly during the procedure, and it was possible to analyse the CPSM scores for 87 women (81 %). The CPSM scores were all linearly related to the VRS. The peak pain score on the CPSM (CPSM-PPS) had the strongest correlation with the VRS score for all three procedures. Higher CPSM-PPS was related to patient (in)tolerance to the procedure ( p = 0.03–0.002). Anxiety at baseline was not correlated with pain perception, except for VRS during colposcopy ( r = 0.39, p = 0.016). Conclusion: The majority of patients were able to use the CPSM correctly, resulting in detailed information on pain perception for each individual pain stimulus during three outpatient gynaecological procedures. The CPSM-PPS had the strongest correlation with the VRS score and patient (in)tolerance to the procedure.